PENGARUH KUALITAS PRODUK DAN KERAGMAN PRODUK TERHADAP LOYALITAS KONSUMEN PADA UD. YULI MAKMUR DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING DI KABUPATEN SITUBONDO - Safitri, Nurul Gita; Fandiyanto, Randika; Wiryaningtyas, Dwi Perwitasari (Fakultas Ekonomi dan Bisnis, 2022)
Marketing is a business activity designed to meet the needs of thecommunity with mutual benefit, just as producers and consumers providereciprocity of their needs. Marketing strategy is the effort of business actors inmarketing activities and target markets to achieve company goals through amarketing mix that includes Product Strategy, Price, Distribution and Promotion.The purpose of this study was to analyze and test the effect of marketing strategyon increasing product sales at UD. Yuli Prosperous. The population in this studywere all UD consumers. Yuli Makmur who is in Situbondo Regency. The moneysampling technique used is a probability sampling technique with a simplerandom sampling method. Data analysis and hypothesis testing in this study usedthe Smart PLS 3.0 (Partial Least Square) application with the Structural EquationModel.The results of the direct influence hypothesis test using the Smart PLS 3.0application, show that product quality has a significant positive effect onconsumer satisfaction, product diversity has a significant positive effect onconsumer satisfaction, product quality has a positive but not significant effect onconsumer loyalty, product diversity has a significant positive effect on consumerloyalty and consumer satisfaction has a significant positive effect on consumerloyalty. The results of the indirect effect hypothesis test using the Smart PLS 3.0application, show that product quality has a significant positive effect onconsumer loyalty through consumer satisfaction and product diversity has asignificant positive effect on consumer loyalty through consumer satisfaction.